2023
DOI: 10.3390/pr11041061
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Thermodynamic Assessment of the Ternary Al–Ni–Er System

Abstract: Al–Ni–Er is an essential system in heat-resistant Al alloys. However, the aluminum-rich corner of this system, which has the most practical application significance, has not been fully studied. In this work, the phase equilibria of the Al–Ni–Er system are investigated via experiments and thermodynamic modeling. The isothermal sections of the Al-rich corner of this ternary system at 600 and 700 °C were determined through equilibrated alloys combined with scanning electron microscopy (SEM), electron probe microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The study by Gan et al [15] shows that trace amounts of Co addition (0.1 at%) could refine the Al 3 Ni fibers under both normal gravitational and super-gravitational fields. Sankanit et al [16] found that the eutectic Al 3 Ni phases could be transformed into a Al 9 (Ni,Mn) 2 phase by adding Mn into Al-Ni alloy; the Al-4Ni-1Mn-0.36Sc-0.06Zr alloy exhibited excellent thermal stability up to a maximum temperature of 350 • C. Rare earth elements such as Yb [17], Sc [18], and Er [19] could effectively refine the microstructure and improve the properties of Al-Ni alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Gan et al [15] shows that trace amounts of Co addition (0.1 at%) could refine the Al 3 Ni fibers under both normal gravitational and super-gravitational fields. Sankanit et al [16] found that the eutectic Al 3 Ni phases could be transformed into a Al 9 (Ni,Mn) 2 phase by adding Mn into Al-Ni alloy; the Al-4Ni-1Mn-0.36Sc-0.06Zr alloy exhibited excellent thermal stability up to a maximum temperature of 350 • C. Rare earth elements such as Yb [17], Sc [18], and Er [19] could effectively refine the microstructure and improve the properties of Al-Ni alloys.…”
Section: Introductionmentioning
confidence: 99%